Ovaries of Lumbricidae earthworms (Annelida, Crassiclitellata), from morphology to ultrastructure - D. Raś; C. Csuzdi; A. Z. Urbisz; Ł. Gajda; K. Małota; P. Świątek (The European Zoological Journal)
Earthworm (Megadrili) ovaries are paired organs located usually in the XIII segment. So far, only their localization and general morphology are well known. Light, fluorescence, and electron microscopy analyses were carried out to describe ovary histology and ultrastructure in selected representatives of the family Lumbricidae. We studied 12 species from six genera: Aporrectodea, Dendrobaena, Eisenia, Lumbricus, Octolasion, and Proctodrilus. It was revealed that Lumbricidae ovaries are tiny, leaf-like structures with one string consisting of growing oocytes. Morphologically, ovaries can be divided into a proximal part (much wider and attached to the septum) and a distal part (more narrow and containing growing oocytes that form an egg string at the end of the ovary). Ovaries are built from germ cells united into numerous syncytial cysts accompanied by somatic cells. Clustering cells are interconnected via intercellular bridges to the poorly developed central cytoplasmic mass (reticular cytophore). According to the histological and ultrastructural results, ovaries can be divided into three zones. Zone I contains oogonia and early-meiotic cells that are already interconnected into cysts, in which all cells develop synchronously. In zone II, germ cells enter diplotene and lose synchrony; most probably, one cell detaches from the given cyst, continues meiosis, gathers nutrients, grows, and becomes an oocyte, whereas the rest of the cells do not grow and become nurse cells. Zone III consists of growing (vitellogenic) oocytes accompanied by cysts interconnecting nurse cells and enveloped by somatic follicular cells. Such an ovary organization is known as the “Dendrobaena” type. Although there are minor differences in ovary morphology between the studied species, no differences were found in their internal organization. Thus, it is postulated that “Dendrobaena” ovaries are characteristic of all lumbricids. Among earthworms, “Dendrobaena” ovaries occur in hormogastrids and most probably in other families closely related to lumbricids.